Dynamic Governance and Investment Climate Development in Gorontalo, Indonesia: An Adaptive Approach to Investment - Kokalo, Milawati; Aneta, Asna; M. Wantu, Fence; Aneta, Yanti (Iapa Proceedings Conference, 2024)
This study examines the application of Dynamic Governance in the investment climate development program in Gorontalo Province. The concept of Dynamic Governance includes adaptive and proactive governance in dealing with economic dynamics. The purpose of this study is to evaluate the effectiveness of local government policies in encouraging investment by considering factors such as regulations, infrastructure, and coordination between institutions. This research uses a qualitative approach through in-depth interviews with government officials, business actors, and investors. The results show that although Dynamic Governance has great potential in improving the investment climate, some key challenges still need to be overcome. These challenges include frequently changing regulations, weak cross-sectoral coordination, and inadequate infrastructure. These findings highlight the importance of more flexible, innovative, and participatory policies, as well as the need to increase the digitalization of licensing services to improve efficiency and transparency. This study contributes to the theory of Dynamic Governance by showing that dynamic governance can help local governments respond to investment challenges more effectively. The strength of this research lies in its in-depth and comprehensive qualitative approach, while its weakness is the limited scope of data that only focuses on Gorontalo Province. The results of this research are expected to be the basis for local governments in creating policies that are more responsive and relevant to the needs of investors.